Analysis of Competence, Discipline, Organizational Culture, and Environment's Impacts on Work Productivity - Wicaksono, Erwin (Sekolah Menengah Kejuruan (SMK) Pustek, 2023)
Good performance support from each employee through work attitudes and behavior will be able to produce productivity high, so that the goals of the company will be more easily achieved and well realized. This study aims to examine the effect of competence, discipline, organizational culture and work environment on the work productivity of PT. Armaz Insan Mandiri. This type of research uses quantitative descriptive statistical methods by distributing questionnaires, analyzing and processing them with statistical methods using SPSS version 26. The population in this study are all employees at PT. Armaz Insan Mandiri, totaling 140 people and taking research samples by means of simple random sampling to employees aged between 21-40 years as many as 104 respondents. The results of the study simultaneously related to the influence of competency, discipline, organizational culture and work environment variables on the work productivity of employees of PT. Armaz Insan Mandiri concluded that there is a positive and significant effect of competency, work discipline and organizational culture simultaneously on work productivity